Inclusive growth in India - learning from best practices of selected countries - Suresh Chand Aggarwal; Divya Satija; Shuheb Khan (Indian Council for Research on International Economic Relations (ICRIER), 2019)
Globally, there is a clamour for creating a more inclusive world and India is also a frontrunner. Government of India is fully committed to its resolve towards achieving inclusive growth. To achieve this goal, efforts are being made to harmonise the national development priorities with international efforts and a number of policies, strategies, programmes / schemes and actions have been implemented at the national level. In this context, this paper analysis India's current position in achieving inclusive growth and sustainable development vis-a-vis 17 selected developed and developing countries including the Turkey, South Africa, Mexico, Brazil, China, Korea, Indonesia, United States, United Kingdom, Australia, France, Canada, Indonesia, Argentina, Russia, Italy, Germany and Japan. The paper is based on an in-depth analysis of secondary information. A comparative analysis of India's inclusive growth position is done with that of the selected countries through a comparison of scores and ranking of these countries vis-a-vis India's position, across key policy and outcome indicators of inclusive growth. In addition, the paper presents specific policies that have a positive impact on both growth and inequality, and that can be the focus of policy action to achieve inclusive growth across different sectors in India. Based on this analysis, best practices that India can adopt have been identified.
Keywords: O15; O19; O23; O38; O40; O57; P46; Q01; 330; Inclusive Growth; Sustainable Development; Development; Fiscal Policy; Equity